2007
DOI: 10.1016/j.jcrs.2007.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of epithelial integrity and cell viability in epithelial flaps prepared with the epi-LASIK procedure

Abstract: Most basal cells in epithelial flaps prepared with different epikeratome devices were dead.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…Second, Tanioka et al [18] found that most basal cells in epithelial flaps were dead, which conflicts with the histological findings reported by Pallikaris et al [13]. Tanioka et al [18] postulated that most basal cells in epithelial flaps are not viable, and that this dead basal cell layer collapses during the immediate postoperative period (POD 1–2) to be replaced by migration and proliferation of adjoining healthy basal cells.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Second, Tanioka et al [18] found that most basal cells in epithelial flaps were dead, which conflicts with the histological findings reported by Pallikaris et al [13]. Tanioka et al [18] postulated that most basal cells in epithelial flaps are not viable, and that this dead basal cell layer collapses during the immediate postoperative period (POD 1–2) to be replaced by migration and proliferation of adjoining healthy basal cells.…”
Section: Discussionmentioning
confidence: 97%
“…It has recently been concluded that most of the epithelial cells were morphologically normal, with minor degeneration of cells after formation of an epithelial flap [20]. Some reports noted that although the corneal epithelium appeared to be normal immediately after surgery, on POD 1 it showed fewer basal cells and did not firmly adhere to the underlying stromal bed [17,18]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] It has been proposed that the presence of the flap reduces postoperative pain and development of corneal haze, though this has not been confirmed in clinical studies. 11,12 It has also been debated that the presence of epithelial cells in the flap may actually hinder the migratory phase of epithelial regeneration and delay the visual recovery.…”
Section: Discussionmentioning
confidence: 99%